2021
DOI: 10.1101/2021.12.03.471024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictions of the SARS-CoV-2 Omicron Variant (B.1.1.529) Spike Protein Receptor-Binding Domain Structure and Neutralizing Antibody Interactions

Abstract: The genome of the SARS-CoV-2 Omicron variant (B.1.1.529) was released on November 22, 2021, which has caused a flurry of media attention due the large number of mutations it contains. These raw data have spurred questions around vaccine efficacy. Given that neither the structural information nor the experimentally-derived antibody interaction of this variant are available, we have turned to predictive computational methods to model the mutated structure of the spike protein's receptor binding domain and posit … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
4
21
0
1
Order By: Relevance
“…Whereas previous variants contained fewer mutations in the S protein and with clear effects on both binding and dynamics (such as N501Y containing variants), Omicron has a larger set of mutations (with more potential for errors in modelling for example) that brings about more mixed results (larger VDS but weaker predicted binding). As the results obtained by Ford et al [21] and those presented here are in agreement, we believe that ignoring insertions and deletions does not substantially impact our results. Considering the fast execution time for our BIS analysis, which makes it possible to analyse large datasets of antibodies, we plan to increase this dataset as more S-antibody structures become available to monitor DS, VDS and BIS for future variants of concern.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas previous variants contained fewer mutations in the S protein and with clear effects on both binding and dynamics (such as N501Y containing variants), Omicron has a larger set of mutations (with more potential for errors in modelling for example) that brings about more mixed results (larger VDS but weaker predicted binding). As the results obtained by Ford et al [21] and those presented here are in agreement, we believe that ignoring insertions and deletions does not substantially impact our results. Considering the fast execution time for our BIS analysis, which makes it possible to analyse large datasets of antibodies, we plan to increase this dataset as more S-antibody structures become available to monitor DS, VDS and BIS for future variants of concern.…”
Section: Discussionsupporting
confidence: 92%
“…The A recent preprint [21] utilized AlphaFold [22] to model the Omicron S protein and the proteinprotein docking software Haddock [23] to predict S-Antibody interactions for four antibodies. It is unclear how small variations in local structure of S as modelled by AlphaFold or of S-antibody complexes as a result of the docking simulation may affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Pulliam and co-workers performed a retrospective analysis on epidemiological data which indicated that the Omicron variant is associated with an increased ability to evade immunity from previous SARS-CoV-2 infection ( 199 ). Computational predictions have further indicated that the structural changes may decrease antibody interaction but not completely evade neutralizing antibodies ( 200 ).…”
Section: Sars-cov-2 Variantsmentioning
confidence: 99%
“…Simulations with the fragment of the original mAbs CR3022 (P00) were also performed for comparison. All these simulations were repeated for RBDs built up with sequences with different mutations of interest present in reported variants (see step 7 in Figure 1 (Kappa/B.1.617.1), (i) G339D, S371L, S373P, S375F, K417N, N440K, G446S, S477N, T478K, E484A, Q493R, G496S, Q498R, N501Y, Y505H (Omicron/B.1.1.529), and (j) Y453F (mink) (Annavajhala et al, 2021, p. 526;Callaway, 2021;Deng et al, 2021;Ford et al, 2021;Khateeb et al, 2021). The input structures with the mutations in the SARS-CoV-2 RBDs were prepared with "UCSF Chimera 1.15" (Pettersen et al, 2004) by the simple replacement of the amino acid followed by a minimization with default parameters and considering the H-bonds (Pettersen et al, 2004).…”
Section: A Fast Constant-ph Coarse-grained (Cg) Approach For Free Energy Calculations On a Large Scalementioning
confidence: 99%